2000
DOI: 10.1117/12.386632
|View full text |Cite
|
Sign up to set email alerts
|

Video Quality Experts Group: current results and future directions

Abstract: Subjective assessment methods have been used reliably for many years to evaluate video quality. They continue to provide the most reliable assessments compared to objective methods. Some issues that arise with subjective assessment include the cost of conducting the evaluations and the fact that these methods cannot easily be used to monitor video quality in real time. Furthermore, traditional, analog objective methods, while still necessary, are not sufficient to measure the quality of digitally compressed vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(68 citation statements)
references
References 4 publications
0
61
0
5
Order By: Relevance
“…The simplest one is a linear function. There are also more sophisticated monotonic functions, such as a third-order polynomial function with monotonicity constraints [27], an S-shaped function [28], a four-parameter logistic function [29], and a five-parameter logistic function [30], [31]. Parameters of these functions are estimated by regression analysis between MOS and the corresponding quality measure in a database.…”
Section: B Nonlinear Mappingmentioning
confidence: 99%
“…The simplest one is a linear function. There are also more sophisticated monotonic functions, such as a third-order polynomial function with monotonicity constraints [27], an S-shaped function [28], a four-parameter logistic function [29], and a five-parameter logistic function [30], [31]. Parameters of these functions are estimated by regression analysis between MOS and the corresponding quality measure in a database.…”
Section: B Nonlinear Mappingmentioning
confidence: 99%
“…Testers rated video sequences affected by different degradation levels, obtained using the proposed exposure generation model. Similarly to the CONTENT 2009 experimental set-up (described in Section 5.1), four test sequences, provided by the VQEG [19], were used: "Betes", "Autumn", "Football", and "Susie". The video sequences reflected two different content characteristics (i.e.…”
Section: Indect 2011 Experimental Setupmentioning
confidence: 99%
“…13 However, despite these oft cited criticisms of MSE-based quality measures there has been a recent resurgence of SNR/PSNR metrics. 17,18 For example, studies of the video quality expert Group ͑VQEG͒ 17 have shown that the PSNR measure is a very good indicator of subjective preference in video coding.…”
Section: A11 Minkowsky Metricsmentioning
confidence: 99%
“…Obviously such quality monitoring can only be realized with objective methods. 17,18 It must be pointed out, however, that subjective assessment, albeit costly and time consuming, if not impractical, is accurate. Objective methods, on the other hand, can at best try to emulate the performance of subjective methods, and utilize knowledge of the human visual system.…”
Section: Introductionmentioning
confidence: 99%